The Influence Beyond Center and Circle Time Method t on Learning Discipline in Children Aged 5-6 Years Through Family Role Playing Centers in RA. Kesuma Elkaemde Namorambe - Fahdia; Juli Yanti Harahap (International Journal of Educational Research Excellence (IJERE), 2022)
This study aims to determine how much influence the beyond center circle time method has on learning discipline in children aged 5-6 years through the family role playing center at RA Kesuma Elkaemde Namo Rambe. This type of research is quantitative research (experimental) with a pre-experimental design, namely one group pretest-posttest. Collecting data using non-test, namely structured observation. The research sampling technique was purposive sampling, namely the sample in this study were children aged 5-6 years in group B, totaling 16 people consisting of 9 boys and 7 girls. The data analysis technique is descriptive analysis. The results of the research show that there is a significant effect of the beyond center and circle time method on the learning discipline of children aged 5-6 years. This is in accordance with the results of the hypothesis test Tcount> Ttable ( 4.009> 1.753) HO is rejected and Ha is accepted. That is, it can be concluded that there is a significant effect of the beyond center and circle time method on children's learning discipline in playing family roles.